2004
DOI: 10.1111/j.1464-410x.2004.04823.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic live‐donor nephrectomy: modifications for developing nations

Abstract: Authors from Lucknow describe their experience with laparoscopic live‐donor nephrectomy, and describe modifications they have used to make the procedure cost‐effective for developing nations. As the urological world is increasingly realising, this approach to renal transplantation is increasing the number of live‐donor kidneys being offered for the many patients with end‐stage renal failure. In this considerable series, the authors are strongly of the opinion that this is the best approach to live donor nephre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…Three surgeons performed all the surgeries. Surgeon A, who headed the program, described the modified iliac fossa incision technique [8] . Surgeons B and C also removed the kidney via this incision but preferred the Pfannenstiel incision.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three surgeons performed all the surgeries. Surgeon A, who headed the program, described the modified iliac fossa incision technique [8] . Surgeons B and C also removed the kidney via this incision but preferred the Pfannenstiel incision.…”
Section: Methodsmentioning
confidence: 99%
“…A fourth 5-mm laparoscopic port was used for retraction and was placed 4 cm below the costal margin in anterior axillary line. Dissection was carried out by our technique as described before and the renal pedicle and ureter were readied for division [8] . The lower polar fat was left intact to ease the delivery of the kidney.…”
Section: Methodsmentioning
confidence: 99%
“…At least 3-4 liters of fluid was given during surgery to negate the effect of pneumoperitoneum [8] . The adrenal and lumbar veins were clipped and divided, and the renal vein was mobilized.…”
Section: Technique Of the Left Transperitoneal Approachmentioning
confidence: 99%
“…In the initial part of our experience (42 cases), we used suture ties to take control of renal vessels, and kidney was extracted from an incision in the flank overlying the fourth port. Later on in the series (17 cases) Endo GI stapler and further on (283 cases) Hem-o-lock clips were used to control renal vessels, and kidney was extracted via the 2-finger technique through the third port [8] . A fan retractor was used to push the kidney down towards the iliac fossa, enabling it to reach the spinoumbilical port.…”
Section: Technique Of the Left Transperitoneal Approachmentioning
confidence: 99%
“…Multiple studies have shown both related and unrelated living donors have similar results in graft and patient outcomes as long as an adequate immunosuppressive protocol is followed [23][24][25][26]. Where local conditions allow, laparoscopic living-donor nephrectomy could be the preferred method as it is as cost-effective as open procedures [27] even in low to middle-income countries [28,29].…”
Section: Discussionmentioning
confidence: 99%